2020
DOI: 10.3390/coatings10010057
|View full text |Cite
|
Sign up to set email alerts
|

Dextran-Thyme Magnesium-Doped Hydroxyapatite Composite Antimicrobial Coatings

Abstract: The dextran-thyme magnesium-doped hydroxyapatite (10MgHAp-Dex-thyme) composite layers were prepared by a dip-coating procedure from stable suspensions and further analyzed for the first time. Different characterization techniques were employed to explore the physical-chemical features of the 10MgHAp-Dex-thyme suspensions and derived coatings. Information regarding the 10MgHAp-Dex-thyme suspensions was extracted on the basis of dynamic light scattering, zeta potential, and ultrasound measurements. The crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 66 publications
8
13
0
1
Order By: Relevance
“…Moreover, the data suggested that the samples started inhibiting the CFU development for all tested strains from 8 h of incubation. These results are in good agreement with our previous studies regarding the influence of magnesium doped hydroxyapatite suspensions and magnesium doped hydroxyapatite enhanced with thyme essential oil in dextran matrix solutions and composite layers on the development of microbial biofilms [24,30]. The results obtained in our previous reported studies [30] suggested that the 10MgHAp-Dex-thyme suspensions presented strong antimicrobial properties even after 24 h in the case of Gram-negative P. aeruginosa and Gram-positive S. aureus bacterial strains.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, the data suggested that the samples started inhibiting the CFU development for all tested strains from 8 h of incubation. These results are in good agreement with our previous studies regarding the influence of magnesium doped hydroxyapatite suspensions and magnesium doped hydroxyapatite enhanced with thyme essential oil in dextran matrix solutions and composite layers on the development of microbial biofilms [24,30]. The results obtained in our previous reported studies [30] suggested that the 10MgHAp-Dex-thyme suspensions presented strong antimicrobial properties even after 24 h in the case of Gram-negative P. aeruginosa and Gram-positive S. aureus bacterial strains.…”
Section: Resultssupporting
confidence: 92%
“…Besides, in our anterior study [24], we certified with ultrasound measurements that a value of −17 ± 3.4 mV of ζ-potential obtained for 10MgHAp in water indicates that the suspension is unstable. Moreover, in recent studies on "Dextran-thyme coated magnesium doped hydroxyapatite layers on glass substrate" [30], ultrasound measurements confirmed that, for a value of −37 mV of the ζ-potential, the suspension has a good stability.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations